2021
DOI: 10.1016/j.biortech.2021.124998
|View full text |Cite
|
Sign up to set email alerts
|

Progress in osmotic membrane bioreactors research: Contaminant removal, microbial community and bioenergy production in wastewater

Abstract: Renewable energy, water conservation, and environmental protection are the most important challenges today. Osmotic membrane bioreactor (OMBR) is an innovative process showing superior performance in bioenergy production, eliminating contaminants, and low fouling tendency. However, salinity build-up is the main drawback of this process. Identifying the microbial community can improve the process in bioenergy production and contaminant treatment. This review aims to study the recent progress and challenges of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…The abundance of Candidatus saccharibacteria, Bacteroidetes, and Firmicutes increased in the samples from both of the two reactors on day 10, while the Proteobacteria abundance decreased. It has been reported that Candidatus saccharibacteria prefers to enrich with complex carbon sources [39]. As domestication proceeded, Candidatus saccharibacteria showed obvious differences in the control and fermentation broth-added treatments and was much higher in the fermentation broth-added treatment on day 20.…”
Section: Community Dynamics Of Activated Sludgementioning
confidence: 93%
“…The abundance of Candidatus saccharibacteria, Bacteroidetes, and Firmicutes increased in the samples from both of the two reactors on day 10, while the Proteobacteria abundance decreased. It has been reported that Candidatus saccharibacteria prefers to enrich with complex carbon sources [39]. As domestication proceeded, Candidatus saccharibacteria showed obvious differences in the control and fermentation broth-added treatments and was much higher in the fermentation broth-added treatment on day 20.…”
Section: Community Dynamics Of Activated Sludgementioning
confidence: 93%
“…The RGO prepared by chemical reduction was highly efficient with satisfying quality in comparison of RGO obtained by nonchemical reduction methods [61,62]. However, difficulties of scalability and the time-consuming process are hindrances.…”
Section: Chemical Reductionmentioning
confidence: 98%
“…Various hybrid and integrated MBR configurations have been explored [80][81][82]. Keerthi et al [83] have a reported hybrid MBR consisting of integrated electrocoagulation, biological, and microfiltration processes for the treatment of ternary effluents.…”
Section: Hybrid Systems Mbrsmentioning
confidence: 99%